Art Music by Caribbean Composers: Barbados - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Owing much to its dual heritage, Barbadian culture is a mix of primarily African and British traditions. Unique forms of indigenous folk music include tuk and spouge music. Tuk music, a local version of the common fife-and-drum marching band, dates back to the 18th century (Bilby, 2008). Tuk music is “lively, with an intricate, pulsating and quick rhythm” (Marshall & Watson, 2008, p. 347). Spouge is a 20th century development (Best, 2005). The Crop Over festival, which originated during colonial times as a harvest festival and which was revived in the 1970s as both a cultural and commercial event, provides an annual venue for traditional and popular music as well as other cultural activities.